2011
DOI: 10.4319/lo.2012.57.1.0043
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simulation of lake and ice dynamics during winter

Abstract: An ice-formation algorithm is implemented in the three-dimensional Estuary and Lake Computer Model, to allow simulation of hydrodynamics and the thermal structure beneath the ice during winter. The one-dimensional governing equation of heat conduction among the three layers of white ice, blue ice, and snow is solved for the formation of ice cover considering the heat flux through air and water. This algorithm is applied independently in each grid cell within the simulation domain, allowing for spatially variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
2
41
0
1
Order By: Relevance
“…We have shown that for temperate mid-latitude lakes, capturing these interactions requires modeling the effects of transient mid-latitude meterological processes, such as snowmelt due to rain and variation of snow and ice albedo, because these lead to relatively rapid changes in the characteristics of the snow and ice layers. Changes in these layers ultimately influence the heat fluxes to the underlying water column and the resultant winter circulation dynamics (Wang et al, 2010;Oveisy et al, 2012;Yang et al, 2012;Kirillin et al, 2012); therefore, accurate estimation of these parameters is very important. The model accuracy in Harmon Lake (ice thickness, MBD=-1.1% and RMSD=0.01 m; snow thickness, MBD=-3.1 % and RMSD=0.02 m) is higher than in previous 1D simulations of lake ice (e.g., Rogers et al, 1995: ice thickness, MBD=-10.6% and RMSD=0.06 m; snow thickness, MBD=-9.6% and RMSD=0.03 m; Patterson and Hamblin, 1988: ice thickness, MBD=52.9% and RMSD=0.14 m; snow thickness, MBD=22.3% and RMSD=0.07 m).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that for temperate mid-latitude lakes, capturing these interactions requires modeling the effects of transient mid-latitude meterological processes, such as snowmelt due to rain and variation of snow and ice albedo, because these lead to relatively rapid changes in the characteristics of the snow and ice layers. Changes in these layers ultimately influence the heat fluxes to the underlying water column and the resultant winter circulation dynamics (Wang et al, 2010;Oveisy et al, 2012;Yang et al, 2012;Kirillin et al, 2012); therefore, accurate estimation of these parameters is very important. The model accuracy in Harmon Lake (ice thickness, MBD=-1.1% and RMSD=0.01 m; snow thickness, MBD=-3.1 % and RMSD=0.02 m) is higher than in previous 1D simulations of lake ice (e.g., Rogers et al, 1995: ice thickness, MBD=-10.6% and RMSD=0.06 m; snow thickness, MBD=-9.6% and RMSD=0.03 m; Patterson and Hamblin, 1988: ice thickness, MBD=52.9% and RMSD=0.14 m; snow thickness, MBD=22.3% and RMSD=0.07 m).…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional modeling of Harmon Lake using ELCOM (Oveisy et al, 2012) showed similar accuracy in predicting ice thickness (RMSD=0.01 m), snow thickness (RMSD=0.02 m), and temperature profiles (MBD=1.23% and RMSD=0.40°C) to the current 1D model using similar ice formation algorithms, confirming that in small lakes with simple geometries, a 1D vertical model can estimate ice and snow thickness and, therefore, inter-annual temperature dynamics, as accurately as a 3D model. This has implications for the inclusion of the many small mid-latitude lakes in climate models (Mackay, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In small lakes, 3D hydrodynamic modelling has been performed to investigate the fate and transport of buoyant storm-river water and the implications of plume mixing dynamics on lake ecological functioning [56]. Other recent studies have investigated the effects of ice layers on small lake hydrodynamics and thermal structure [50], and the effect of wind-driven circulation on phytoplankton distribution [68]. However, the 3D modelling of small upland lakes remains uncommon, probably because 1D models are considered adequate to resolve the evolution of lake thermal structure at seasonal and longer timescales [19].…”
Section: Introductionmentioning
confidence: 99%